The Influence Of Flash Card Media Usage On The Ability To Memorize English Vocabulary For Third Grade Students Of Inpres Perumnas Antang III Elementary School - Farika, Syahgita Putri; Pagarra, Hamzah; Hermuttaqien, Bhakti Prima Findiga (Program Studi PGSD FIP UNM, 2025)
This study aims to describe the use of flash card media in improving the quality of English learning, to assess the vocabulary memorization skills of third-grade students, and to analyze the impact of flash card media on those skills. The research was conducted at SD Inpres Perumnas Antang III using a quantitative approach with a quasi-experimental design in the form of a non-equivalent control group. The subjects consisted of 31 students divided into an experimental group and a control group. The results showed that the use of flash cards positively influenced the quality of English learning. Students became more active, enthusiastic, and engaged in the learning process. Flash cards, which featured attractive visuals and accompanying audio, effectively enhanced student focus and motivation in memorizing vocabulary. In addition, students' vocabulary mastery significantly improved after learning with flash cards. Based on the pre-test and post-test results, the average score increased from 66.48 to 94.19. Most students demonstrated strong abilities in recognizing, pronouncing, and using vocabulary in simple sentence contexts. Inferential analysis using N-Gain and T-Test confirmed that flash card media had a significant effect on vocabulary memorization skills. The N Gain score reached 83.97%, classified as high effectiveness, and the T-Test showed a statistically significant difference between pre-test and post-test results (p < 0.05). Therefore, flash cards are proven to be an effective learning strategy to support vocabulary development among elementary school students.